Endangered man and the reply of the Christian from the juridical viewpoint* - Zyl, F. J. van (Koers, 1979)
The central theme of this series of lectures implies that man — and then especially modern man, who provokes our concern — is an endangered being and that the Christian has a reply to this threat. I have been accorded the signal honour of being asked to evaluate the problem from the point of view of the Law. I would like to extend my cordial appreciation to the PU for CHE for this invitation. There can be no doubt as far as the first implication goes, which is that man is an endangered being. The second implication, which claims that the Christian always has an answer, is more problematic, especially if one looks at the central theme from the point of view of Law.